Phase Transition Originating from Disorder–Order Transformation Coupled with Reorientation in the Organic–Inorganic Hybrid Compound (C4H14N2)[Cd2(H2O)6(SO4)3]. Issue 5 (6th February 2017) - Mu, Rong; Chen, Chun‐Hong; Zhang, Li; Jia, Dian‐Zeng; Xu, Guan‐Cheng
Abstract : The organic–inorganic hybrid compound 1, 4‐butyldiammonium hexaaquadicadmium(II) trisulfate (C4 H14 N2 )[Cd2 (H2 O)6 (SO4 )3 ] (1 ) was synthesized by the reaction of 3CdSO4 · 8H2 O with 1, 4‐butanediamine in sulfuric acid aqueous solution. Differential scanning calorimetry measurements indicate that1 undergoes a reversible phase transition at 243.4 K with a thermal hysteresis of 3.3 K. Single‐crystal X‐ray diffraction data disclose that the phase transition is from the room‐temperature phase with the space group C 2/ c to the low‐temperature phase with the space group P 1 with the Aizu notation of 2/ mF 1 . The structural phase transition of1 is ascribed to the coupling of disorder–order transformations of the flexible 1, 4‐butyldiammonium cation and a sulfate anion and reorientation of the cation. The temperature dependence of the dielectric permittivity demonstrates a step‐like change in the range 200–260 K, which makes (C4 H14 N2 )[Cd2 (H2 O)6 (SO4 )3 ] a promising switchable dielectric material. The results could offer an avenue to design switchable dielectric materials through the synergistic effect of disorder–order transitions and reorientation motion. Abstract : The compound (C4 H14 N2 )[Cd2 (H2 O)6 (SO4 )3 ] undergoes a reversible phase transition at around 243.4 K. Disorder–order transformations of the 1, 4‐butyldiammonium cation and sulfate anion together with reorientation of the cation induce the phase transition. The step‐like dielectric response makes the compound an excellent candidate for switchable dielectric materials.